Numerical modeling of the seismic performance of monopile supported wind turbines in sandy soils susceptible to liquefaction. - Tirandazian, Mehran; Nouri, Gholamreza (International Journal of Engineering and Technology, 2018)
Since 1980, as wind farms have moved from coastal to offshore areas, the wind energy industry has been completely transformed which in turn has led to the increase in the construction of wind turbines. On the other hand, harsher offshore environmental conditions have led to larger lateral loads and anchorages applied to the wind turbines and specifically to their piles than other coastal and offshore structures. Thus, more solid piles are required to ensure proper rigidity and bearing capacity. Liquefaction is one of the most important seismic hazards through which various damages caused to different parts of wind turbines. In order to develop coastal and offshore structures in Iran, a study of liquefaction is of great importance due in part to the high risk of seismicity. In this study, the effect of liquefaction on seismic response of offshore wind turbines is examined taking advantage of a finite element model. To this end, all analyzes have been carried out in both occurrence and non-occurrence of the liquefaction, so that by comparing these two modes, the mechanisms affecting the seismic behavior of wind turbines are understood. As depth increases, the possibility of liquefaction is reduced due to higher pressure. Liquefaction is considered to a depth of 20 m and structural behavior is evaluated based on the level of seismic hazard, the thickness of the susceptible layers, soil compaction, the non-fluidizing top layer, the gradient of the earth, the thickness of the monopole, the dimensions of the wind turbine and different soil layering conditions. According to the mentioned factors, a comprehensive and parametric study of the behavior of wind turbines in seismic zones, and in different loading conditions, pile diameters and soil layering is carried out in soils prone to liquefaction. Since analyzes are performed in both occurrence and non-occurrence of the liquefaction, the number of analyzes and computational cost in this research becomes enormous. Therefore, there is a need for a highly effective software and a practical modeling method that will allow for this comprehensive study. Open Sees software and beam on nonlinear Winkler foundation approach are used to model the soil-pile-structure interaction. The minor differences observed in the laboratory values compared to the numerically calculated ones may refer to the fact that the chamber is not modeled. In the bottom layer, as the depth decreases, the elastic response spectra record larger values which are due to the resonance in the structure.Â Â